A cyclic bis[2]catenane metallacage - Wang, Yiliang; Zhang, Yicheng; Zhou, Zhixuan; Vanderlinden, Ryan T.; Li, Bin; Song, Bo; Li, Xiaopeng; Cui, Lei; Li, Jian; Jia, Xueshun; Fang, Jianhui; Li, Chunju; et al. (Nature communications, 2020)
Catenated cages represent chemistry’s challenging synthetic targets because a three-dimensional assembly is necessary for their formation. Herein, a cyclic bis[2]catenane is constructed through the coordination-driven self-assembly of the interlocked bis-metallacage, by the 90° Pt(II) heteroligation of the endo-functionalized double-bridged tweezer bearing pyridyl moieties and the tetra-carboxylated linker. NMR spectrometry, X-ray crystallography and mass spectrometry confirm the formation of a cyclic bis[2]catenane with “∞”-shaped topology via a 14-component self-assembly. Particularly, reversibly responsive transformation between the bis[2]catenane and the bis-metallacage can be realized by guest exchange, concentration effect and solvent effect. This work represents a novel example of a cyclic cage-based [2]catenane oligomer. Catenated cages are challenging synthetic targets in chemistry. Here, the authors employ a multi-component coordination strategy using a Pt(II) heteroligation to construct a cyclic bis[2]catenane metallacage, which could be reversibly transformed between the catenated structure and the bis-metallacage.